Interlanguage Errors In Senior High School Students’ Recount Text Writing - Muhamad Ahsanu (JELLE : Journal Of English Literature, Linguistics, and Education, 2022)
This research is mainly concerned with the analysis of interlanguage errors of senior high school students in writing recount text. The purposes of this research are: to analyze the dominant types of interlanguage errors made by students in their recount text writing under the surface strategy taxonomy, to analyze the reasons why the errors occur to the students in writing their recount text, and to analyze the way interlanguage processes influence students to make errors in writing their recount text. This research used descriptive-qualitative methodology. The samples of this research were 15 eleventh-grade students of MA PK Ma’arif 2 Kuwarasan. The data were collected through documentation, table checklist, and interview. The technique of data analysis was triangulation. The results of this research indicate 1) the four kinds of error based on surface strategy taxonomy (omission, addition, misordering, and misformation); the dominant error that appears in students’ writing recount text is misformation error, 2) the reasons why this error occured, and 3) the three interlanguage processes influencing the students in making errors covering overgeneralization, strategies of second language learning, and language transfer. Keywords: interlanguage, error analysis, recount text writing